Desenvolvimento profissional docente : narrativas de professoras dos anos iniciais sobre experiências de leitura e contação de histórias - Moura, Eliane das Neves (2019)
ABSTRACT The central theme of this research is Storytelling in the beginning grades, at the Tancredo de Almeida Neves municipal School, that offers the first cycle in the literacy program, in Cuiabá. It aims at understanding the professional development of the participating teachers through the narratives of their practices of reading and storytelling, the learning that occurred after the formations, and the challenges and dilemmas related to the storytelling practice in the classroom. It is an investigative study with a qualitative approach, having the narrative as a research method and a phenomenon to be studied, based on Connelly and Clandinin (1995, 2011, 2015). It had as a starting point the concept of teacher training offered by Antônio Nóvoa (1991, 1995, 2000), Day (2001, 2006) and Maria da Graça Mizukami (1992, 2001, 2003, 2012), and John Dewey’s concept of experience (2010). For the discussions on Storytelling, the following authors were used: Câmara Cascudo (2006), Cléo Busatto (2011), Heloísa Prieto (1999), Bia Bedran (2012), Eliana Yunes (2012), and Celso Sisto (2015). Various strategies were used to compose field texts of this research, such as: classroom observations and everyday school life, conversations and narrative interviews, field notes and an implementation of eight formative strategies of storytelling. Through the narrative of the four participants, teachers of the First Grades, I had access to their personal and professional life stories, I identified their reading stories as well as how the construction process of teacher learning occurred during the formations of storytelling. I also observed the sources used to build the necessary learning to work with reading, specially through storytelling in the classroom. The three thematic axes developed, from the participants’ narratives, report of the personal and professional trajectory, the learning narrated during the formations, and also the dilemmas and difficulties. The experiences shared and the stories told by the participants of the research brought into evidence the triggering of a critical-reflexive position toward their practices and theoretical convictions on reading and storytelling, in a movement toward the construction of the new learning, as well as an individual professional development. Besides, they provoked a reflection on the use of stories, not only as a strategy of introducing the different axes of language and the contents of other subjects, but the importance of the narratives (storytelling) was emphasized to stimulate creativity and imagination, orality; as a facilitator of learning in the development of oral, written and visual language, encouraging the pleasure of reading, developing a critical mind, make-believe games, values and concepts that help in the formation of the child's personality, promoting the social and affective development while exploring culture and diversity. They also triggered the reflection on the choice of the story repertoire and of the use of different storytelling strategies.